Pengaruh Pendekatan Etnopedagogi Berbasis Nilai Pappaseng terhadap Pemahaman Materi IPS Pada Siswa Kelas VII SMP Negeri 8 Parepare - Asmaul Husna; Zurahmah Zurahmah; Abd. Rahman K; Jumaisa Jumaisa (JURNAL PENDIDIKAN IPS, 2026)
The ethnopedagogical approach based on pappaseng values is an educational approach that integrates Bugis local wisdom into the learning process and character development. These values include lempu’ (honesty), warani (courage), siri’ na pesse (shame and empathy), sipakatau (humanizing others), and getteng (steadfastness). This study aims to examine the effect of this approach on students’ understanding of social studies (IPS) among seventh-grade students at SMP Negeri 8 Parepare. This research employed a quantitative approach with a correlational design. The sample consisted of 85 respondents selected through purposive sampling. Data were collected through observation, questionnaires, tests, and documentation, and analyzed using descriptive and inferential statistics. The results show that the implementation of the ethnopedagogical approach based on pappaseng values is categorized as good (76%), while students’ understanding of social studies is at a moderate level (73%). Inferential analysis indicates a significant effect with =0,213 at a significance level of  . The contribution of this approach is 9%, while 91% is influenced by other factors. Thus, this approach has a positive effect but still requires further strengthening in its implementation.